2008
DOI: 10.1161/circ.118.suppl_18.s_733-c
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 2476: Regular Physical Activity Prevents the Development of Left Ventricular Hypertrophy in Young Stage 1 Hypertensive Subjects: Results of the Harvest Study

Abstract: A beneficial effect of physical activity on left ventricular mass( LVM) in the short term has been described in hypertension. Aim of this study was to investigate the long-term effect of regular physical activity on development of left ventricular hypertrophy (LVH) in a cohort of young hypertensive subjects. We studied 454 participants (317 men, mean age 33±8 years) without LVH at baseline whose physical activity status was consistent throughout the follow-up. BP was 146±11/94±5 mm Hg at baseline and 141±/90±8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Physical exercise has been proved to improve human health, cardiovascular function, respiratory function and motor system function, and thus reduce the risk of high blood pressure in the middle-aged and elderly. [37,38] Mos L et al [39] recruited 454 hypertensive patients without left ventricular hypertrophy and evaluated the long-term effect of regular PA on the development of left ventricular hypertrophy in hypertensive subjects. The study concluded that regular PA could prevent left ventricular hypertrophy in hypertensive subjects, and both leisure and competitive sports activities could have a positive impact on left ventricular quality in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Physical exercise has been proved to improve human health, cardiovascular function, respiratory function and motor system function, and thus reduce the risk of high blood pressure in the middle-aged and elderly. [37,38] Mos L et al [39] recruited 454 hypertensive patients without left ventricular hypertrophy and evaluated the long-term effect of regular PA on the development of left ventricular hypertrophy in hypertensive subjects. The study concluded that regular PA could prevent left ventricular hypertrophy in hypertensive subjects, and both leisure and competitive sports activities could have a positive impact on left ventricular quality in hypertensive subjects.…”
Section: Discussionmentioning
confidence: 99%